BELIMBING PADA TEMBANG LIR-ILIR SEBAGAI SUMBER INSPIRASI PENCIPTAAN MOTIF PENDOK KRAWANGAN TEMPEL - Pradina, Hesti; Wiyoko, Aji (Sanggitarupa, 2022)
Star fruit is a fruit that lives in a tropical climate, which has a unique shape that has five circles, like stars. The shape of the star fruit is often associated with several symbolic meanings such as leadership, education, religion, morals and others. One of the excerpts from the song Lir-Ilir mentions that star fruit, which is then interpreted as a symbol of the pillars of Islam. The symbolization of star fruit can be an attraction to be developed as a decoration of a keris pendok made with the krawangan paste technique. The method of creating a kris pendok for this Final Project is through the stages: exploration, design, and embodiment. The aesthetic approach of the pendok decoration pays attention to the decorative aspect that describes the symbolic elements, which are adapted to the shape of the bunton keris pendok. The techniques used in forming the decoration are a combination of carving and krawangan carving techniques, soldering techniques, and electroplating techniques. The creation of the pendok kris krawangan outboard has succeeded in making 5 works, each entitled Limo Lingir, Wejangan Sunan Kalijaga, Menek Blimbing, Pillars of Islam and Panca Wiyata Tinembang Lir-ilir. Each pendok work depicts ornamental elements of star fruit combined with the values of the meaning of the Lir-ilir song. The resulting pendok has an artistic impression through a combination of decorative elements, and contains a moral message so that as Muslims uphold the pillars of Islam.